ANALISIS PERSEPSI GURU SEKOLAH DASAR TERHADAP IMPLEMENTASI KURIKULUM MERDEKA - Zahara, Leni; Mawaddah Insani, Viola; Riri; Maisarahtul Ispar; Winda Rabiyatul Adawiyah; Adawiyah; Reni Retista; Roni Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the perceptions of elementary school teachers towards the implementation of Merdeka Curriculum as an educational policy innovation in Indonesia. This curriculum is expected to be able to answer the challenges of post-pandemic education by offering flexibility, project-based learning, and an emphasis on the character of the Pancasila Student Profile. The research used a descriptive qualitative method with a literature study approach, plus field data from observations and interviews during the Real Work Lecture (KKN) at SD Negeri 04 Talang Tangah, West Sumatra. The results showed that teachers generally responded positively to the freedom in designing learning. However, implementation in the field still faces obstacles such as limited facilities, low training participation, and difficulties in integrating character values into teaching materials. In addition, there is still a gap between teachers' understanding and the delivery of materials in the training. Therefore, support is needed in the form of continuous training, equitable access to resources, and comprehensive evaluation to optimize the implementation of Merdeka Curriculum.